If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26(3c + 4) = 2(c + 5) + c Reorder the terms: 26(4 + 3c) = 2(c + 5) + c (4 * 26 + 3c * 26) = 2(c + 5) + c (104 + 78c) = 2(c + 5) + c Reorder the terms: 104 + 78c = 2(5 + c) + c 104 + 78c = (5 * 2 + c * 2) + c 104 + 78c = (10 + 2c) + c Combine like terms: 2c + c = 3c 104 + 78c = 10 + 3c Solving 104 + 78c = 10 + 3c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-3c' to each side of the equation. 104 + 78c + -3c = 10 + 3c + -3c Combine like terms: 78c + -3c = 75c 104 + 75c = 10 + 3c + -3c Combine like terms: 3c + -3c = 0 104 + 75c = 10 + 0 104 + 75c = 10 Add '-104' to each side of the equation. 104 + -104 + 75c = 10 + -104 Combine like terms: 104 + -104 = 0 0 + 75c = 10 + -104 75c = 10 + -104 Combine like terms: 10 + -104 = -94 75c = -94 Divide each side by '75'. c = -1.253333333 Simplifying c = -1.253333333
| 14c^2-33cr+18r^2=0 | | 4+16x=72 | | 5(d+4)=10-5x+3 | | -10-(-7)+4=v | | 9+6x+9x-30= | | 3a^2-3p^2=0 | | 3X+12=4X-2 | | 4f-3+7f=31 | | X+2+4x-142=180 | | 3(2x-1)-3x=15 | | (x-4)=9x-33 | | 64x^2+34x+1=0 | | 5x-1=2+15 | | -2r+4=(-3)+9 | | x-2.5= | | f(t)=-3t^2+24t-36 | | 24+18x=90 | | 5x+2=3+32 | | -9=-3-n | | t^434343-t^434342=0 | | 5x-2=7x-4 | | 10-x=4x+3 | | -1=5x+6/6 | | 5x+135=0 | | 13+6x=3+11x | | 47+0.41666666666x=100 | | (64x^2-1)=0 | | -2x+4=-4x+12 | | 0=3x^2-6x-9 | | 4+7x=5x-18 | | 13x-74=78 | | 2x+4+2x-6=6x+20 |